Representation of Ethnocultural Units in the National Corpus of the Kazakh Language (Eurasian Journal of Philology Science and Education, 2025)
The study of ethnocultural units representing the national identity and culture, lifestyle and spiritual culture of the Kazakh people is a topical issue. The creation of the national corpus contributed to the development of the Kazakh language, which conveys the importance of ethno-cultural units to the young generation living in the modern era of digitalization. In this direction, ethnocultural units of the national corpus of the Kazakh language were chosen as the object of research. The problem of structural-semantic analysis of the representation of cultural names in material values ​​in the system of ethno-cultural units of the national corpus of the Kazakh language is very relevant.The purpose of the research is to describe the national worldview and national identity, which separate the meanings of everyday realia in the objective meaning, by analyzing the representation of ethnocultural units in the national corpus. The quantitative and qualitative representation of  ethnocultural units in the national corpus of the Kazakh language has been analyzed, the ways and methods of introducing ethno-cultural units into the national corpus were described. Methods of modeling, coding and application of algorithmic-programming methods of ethnocultural units for inclusion in the national corpus were described. On the basis of the analysis of the collection and representation of ethnocultural units, when creating the national corpus base, linguistic-semantic, word-formative groups were classified according to the principle of classification. The practical results of the research can be applied by linguists and lexicographers when compiling ethnocultural units and determining their lexical, word-formative and semantic meanings based on the national corpus of the Kazakh language.Keywords: Kazakh language, national corpus, ethnocultural units, word formation, ethnocultural analysis, lexical-semantic analysis.